A SINGLE-BLIND, PLACEBO-CONTROLLED CLINICAL TRIAL OF LOCAL APPLICATION OF KOHL-CHIKNI DAWA-A UNANI COMPOUND FORMULATION IN THE PATIENTS WITH CORNEAL OPACITY - ZAIDI, ZEHRA; NAZIR, SHEHLA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present clinical trial was undertaken to evaluate the safety, preventive/curative efficacy of the local application of Kohl-Chikni Dawa (KCD) in patients with corneal opacity (CO), to provide an economic, safe, and effective alternative treatment for it. Methods: The present prospective single-blind, placebo-controlled trial was undertaken at Majeedia Hospital, Hamdard University, New Delhi. Ninety-two diagnosed patients of CO were randomly allocated to three groups for local application of KCD/placebo two sticks BID. Results: Forty patients completed the 6-month duration of the study. KCD was found effective in the general amelioration of the signs and symptoms of CO. There was a statistically significant reduction in the CO score and improvement in vision on the reading of the Snellen chart in the test drug group in comparison to the placebo group in Grade-I (Nebular type) CO (p>0.05). Conclusion: KCD was found very much effective to reduce the CO score, with clinical improvement of vision in the nebular type of CO. The dose of KCD in two sticks BID was found safe and tolerable with no side effects. A multicentric trial of the test drug on larger sample size for a longer duration is required to establish the efficacy of the formulation on CO.